The Design and Analysis of DC Electrical Voltage-Current Datalogger Device Implemented on Wind Turbine Control System - Murti, Sri; Megantoro, Prisma; Silva, Gabriel De Brito; Maseleno, Andino (Universitas Muhammadiyah Yogyakarta, 2020)
DC electrical voltage - current measuring instrument and data logger is an instrument used to measure the current and voltage generated wind turbine and recording the measurement results. The fuction of this instrument is to activate the dummy load on the wind turbine control system to reduce the voltage that exceeds the safe limit when saving electrical energy. The purpose of this research is to manufacture and analyze DC electrical voltage - current measuring instrument with arduino uno based data logger which is capable to measure DC current and voltage generated by Hybrid Power Plants (PLTH) in Pantai Baru Pandansimo Bantul Yogyakarta, and using metrology method to analyze the degree of uncertainty of the measuring instrument. In this research, heuristic method is used to determine the characteristics of the sensor. Sensor characterization has been done, followed by calibration of measurement instrument to determine the magnitude of the uncertainty of the measurement instrument. The results of this research indicated that the characteristics of voltage sensor (CR5310-300) obtained equation of linear regression y=0.29253x + 0.662, while the current sensor characteristics (WCS1800) obtained equation of linear regression y=0.072978x - 37.2408. After the characterization procedure is done, the measuring instrument callibrated using a traced clampmeter. The calibration results indicated that the voltage sensor has accuracy of 99.99%. Whereas for the current measuring instrument has an uncertainty that is extended at standard current 0 -Â 9 amperes of 0.316 amperes and at the standard current of 9.7 amperes of 0.317 amperes with an accuracy of 99.98%. Based on the results of this research, can be obtained that current and voltage measuring instrument has good accuracy level.